Legal Protection of Buyers in the Sale and Purchase Agreement of Uncertified Pangkalan Mansyur Land - Hutagaol, Delvia Sawita Lestari Br; Simamora, Janpatar (Manunggal Halim Jaya, 2025)
This article discusses legal protection in land sale and purchase agreements in Pangkalan Mansyur conducted informally (underhand) and without certificates. Legal protection is provided through agreement clauses and statutory provisions such as the Civil Code and the Basic Agrarian Law (UUPA). This article highlights the importance of land certificates as legal evidence of legal ownership and the legal risks that arise in transactions without certificates, including land disputes. A normative juridical approach evaluates how legal regulations protect parties in such transactions. In conclusion, land without certificates presents legal challenges, and legal protection must ensure fairness and legal certainty for all parties involved. Educational efforts and ease of land titling are also proposed to reduce the potential for future disputes.